Sifat Kimiawi Hidrolisat Protein Ikan Gabus (Channa striata) - Ika Meidy Deviarni; Evi Fitriyani (JURNAL GALUNG TROPIKA, 2021)
Fish protein hydrolyzate (HPI) is a dry protein dosage form with more than 60% protein content. HPI is produced from breaking down fish protein into simple peptides and amino acids through the hydrolysis process by enzymes, acids, or bases. The HPI snakehead product is expected to increase the product's added value because it can be applied in the food and non-food fields. This study aims to obtain the papain enzyme concentration that produces the best HPI through the total residual solids (%) test and the degree of hydrolysis test. In addition, to get the proximate value of HPI flour with the best papain enzyme. Based on the total residual solids test (%) and the degree of hydrolysis (%), the best value was obtained in the treatment of adding 20% papain enzyme. This resulted in a value of 13.25% water content, 0.045% ash content, 20.81% protein content, and 0.28% fat content.